A mineralogical approach to evaluating laboratory scale acid rock drainage characterisation tests. (September 2015) - Becker, M.; Dyantyi, N.; Broadhurst, J.L.; Harrison, Susan T.L.; Franzidis, J.-P.
Highlights: Development of a mineralogical approach for ARD characterisation. Dissolution of carbonates and intermediate weathering silicates contribute to ANC. Auto-SEM is a valuable tool in ARD characterisation. Abstract: Effective management of the risks associated with acid rock drainage (ARD) requires the ability to identify material with a potential to generate ARD reliably. With the increasing prevalence of quantitative mineralogy (Quantitative XRD, auto-SEM), opportunity exists to use mineralogy at all stages in ARD characterisation and prediction. This study uses a mineralogical approach across the head grade samples and the residues obtained under leach conditions of several common ARD characterisation tests (Acid Neutralising Capacity, Net Acid Generation), as well as the University of Cape Town (UCT) biokinetic test to evaluate the extent to which acid-neutralising minerals react. The results show the contribution of the carbonates to the acid neutralising capacity, as well as the partial dissolution of intermediate weathering silicate minerals such as chlorite and mica.